Quantitative damage imaging in plates based on SH0 mode tomographic approach. Issue 4 (January 2021) - Ahmad, Mubarak; Liu, Zenghua; Basit, Abdul; Bin, Wu; He, Cunfu
Abstract: Exploring the non-dispersive property, the fundamental shear horizontal mode SH0 can be widely used in the detection and monitoring of defects in plate like structures. To combine an approach of ultrasonic guided waves and a tomographic technique by adapting a reconstruction algorithm for the probabilistic inspection of damage (RAPID) using a double-turn coil omnidirectional shear horizontal wave magnetostrictive patch transducer (OSH-MPT) with three different kinds of array arrangements is presented here for imaging. SH0 can propagate in a composite material through bonding double-turn coil OSH-MPT. To get the information about a damage, RAPID can be utilized based on direct wave of SH0 mode. It is advantageous to monitor a composite plate where the velocity of direct waves depends on the propagation direction. In this paper, a surface simulated defect, using a small cylinder, in a composite material is quantitatively evaluated by using shear horizontal mode tomographic approach. Using modified approaches, to eliminate the effect of uneven probability distribution of the array (UPDA) in RAPID, imaging is obtained. Three different array setups of transducers have been tested to monitor the influence on the images. It has been presented that the image generated by the proposed approach with the optimal transducer array and shape factor, β, calculation method has great influence on the real defect shape. To improve the imaging results threshold is selected based on the receiver operating characteristic (ROC) curve. The proposed approach can be used to detect, locate and image the surface defects in plate like structures.